CORRELATION BETWEEN MOTHER’S KNOWLEDGE AND HUSBAND’S SUPPORT WITH THE USE OF IUD IN BOAWAE COMMUNITY HEALTH CENTER - Irmina Tulle; Atika Atika; Baksono Winardi (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: The intrauterine device (IUD) is an effective and efficient long-term method of contraception which has effect of delaying and spacing more than three years of birth. NTT is one of the province with the most dominant short-acting contraception methods usage and IUD contraceptive usage is lowest in Boawae Community Health Center. The low use of IUD can be influenced by two factors such as mother’s knowledge and husband’s support. This study aims to analyse relationship between mother’s knowledge and husband’s support. with the use of IUD. Method: This study was observational analytic study with cross sectional approach. There were 104 mothers consisted of 52 IUDs and 52 non IUDs, were selected by simple random sampling technique and assessed with questionnaire. The independent variable are mother's knowledge and husband's support, while the dependent variable is the use of IUD.  Data analysis was achieved by chi square and multiple regression logistic test. Results: The results showed that most of mothers with IUD had good knowledge as much as 67.3% and most of non-IUDs’s mothers had less knowledge of 40,4%. Husband’s support of mother’s with IUDs was 67,3% and in non-IUD’s mothers was only 15,4%. There were significant association between mother’s knowledge (p value =0,000) and husband’s support (p value = 0,000) with the use of IUD. Multiple logistic regression test showed that husband support was the most dominant factor with p value = 0,000 (p <0.05). Conclusion: There were relationship between knowledge and husband’s support with the use of IUD. Husband's support is the most dominant factor in the use of IUD.